Relation of Drug-Eluting Stent Strut Distribution to Stent Thrombosis in Coronary Arteries - Opolski, Maksymilian P.; Pracon, Radoslaw; Mintz, Gary S.; Okabe, Teruo; Pregowski, Jerzy; Lee, Sung Yun; van der Waal, Eva C.; Kalinczuk, Lukasz; Roy, Probal; Smith, Kimberly A.; Torguson, Rebecca; Xue, Zhenyi; et al. (The American journal of cardiology, 2009)
The distribution of stent struts is critical to drug deposition and, therefore, may affect the amount of neointima and the risk of thrombosis after drug-eluting stent (DES) implantation. The aim of our study was to evaluate stent strut distribution in the setting of a drug-eluting stent thrombosis (ST). We retrospectively analyzed postprocedural intravascular ultrasound (IVUS) images of 13 patients who subsequently developed ST (14 DES thrombotic lesions) and a control group of 27 patients (30 DES lesions) matched for stent type and presence of chronic renal failure. In addition to standard IVUS measurements, visible struts were counted and maximum interstrut angle was measured at 1-mm intervals. Early ST was defined as ≤30 days after DES deployment and late ST as >30 days after DES deployment. Compared with DES controls, the ST group had a larger maximum interstrut angle (60.8 ± 8.3° vs 55.7 ± 4.8°, p = 0.014) and a similar number of stent struts (8.4 ± 0.6 vs 8.7 ± 0.6, p = NS). Maximum interstrut angle tended to be larger in late ST than in early ST (66.1 ± 10.8° vs 57.8 ± 5.0°, p = 0.071). The incidence of maximum interstrut angles ≥90° and ≥120° observed continuously for ≥2 mm of stent length was higher in the ST group (p = 0.009 and p = 0.096, respectively). In conclusion, DES-treated lesions leading to ST had larger maximum interstrut gaps distributed circumferentially and longitudinally, but a similar number of struts at the time of DES implantation compared with DES controls.